New genus and new species of Neoibidionini from the Neotropical region (Coleoptera, Cerambycidae, Cerambycinae) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
One new genus and six new species are described from the Neotropical region: Heterachthes hildebranti, H. skillmani, and H. noguerai, from Mexico; Compsibidion morrisi, from Bolivia; Tropidion wappesi, from Bolivia; and Biraidion, new genus, type species B. martinsi sp. nov., from Bolivia. Biraidion, Compsibidion morrisi, and Tropidion wappesi are included in previous keys.